Global Handbook of Quality of Life: Exploration of Well-Being of Nations and Continents - Glatzer, W (Springer, 2015)
This handbook provides a comprehensive historical account of the field of Quality of Life. It brings together theoretical insights and empirical findings and presents the main items of global quality of life and wellbeing research. Worldwide in its scope of topics, the handbook examines discussions of demographic and health development, the spread of democracy, global economic accounting, multi-item measurement of perceived satisfaction and expert-assessed quality of life and the well-being of children, women and poor people. It looks at well-being in specific regions, including North and Sub-Saharan Africa, Asia, South America and Eastern and Western Europe. In addition to contributions by leading and younger authors, the handbook includes contributions from International Organizations about their own work with respect to social reporting.